Acid Catalyzed Efficient Syntheses of Aryl‐5H‐dibenzo[b, i]xanthene‐5, 7, 12, 14‐(13H)‐tetraones and 3, 3‐(Arylmethylene)bis(2‐hydroxynaphthalene‐1, 4‐diones) and In Vitro Evaluation of their Antioxidant Activity. (5th May 2014) - Khurana, Jitender M.; Lumb, Anshika; Chaudhary, Ankita; Nand, Bhaskara
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>